Towards Universal Health Coverage: Access to Maternal and Child Health Services in Hardto-Reach Areas in a Community Development Block of a Health District, West Bengal, India - Srikanta Chakraborty; Sukumar Mitra; Nibedita Banerjee; Avilash Mondal; Arup Chakraborty; Saptarshi Ghosh (Journal of Clinical and Diagnostic Research, 2021)
Introduction: It is well established that poor economic condition is an important contributor of barrier to accessibility. However, non financial barriers also constitute significant constraints to the equitable access of full range of health services included under national Universal Health Coverage (UHC) policies. Aim: To study the accessibility of Maternal and Child Health Services in remote and hard-to-reach areas towards UHC and also to identify and synthesise non financial access barriers to accessibility of Maternal and Child Health Services and to distinguish them from financial barriers. Materials and Methods: A retrospective, observational study was done using a mixed method approach in the Institute of Public health, Kalyani, Kolkata, West Bengal, India from December 2016 to May 2017. Quantitative analysis of Health Management Information System (HMIS) data along with qualitative study by Focused Group Discussion (FGD) and In-depth Interview (IDI) was performed. Two FGDs were conducted among antenatal mothers and Accredited Social Health Activist (ASHA) workers and IDI was conducted with female health supervisor of that block. The mothers who attended the Subcentre (SC) for checkup on a particular day were asked to participate, and 10 ASHA workers who had come to the rural hospital on that day for monthly meeting were chosen for another FGD, with the help of a structured questionnaire. Results: Quantitative analysis of HMIS reports revealed decreasing trend in utilisation of Maternal and Child Health Services. There were 3048 antenatal registrations in the year 2012-2013, whereas it was 2771 in the year 2016-2017. The number of institutional deliveries was 1166 in the year 2012-2013, whereas it was 471 in the year 2016 to 2017. The number of health service providers also decreased than that of the previous year. Number of skilled birth healthcare providers were 11 in the year 2012-2013, whereas it become reduced to zero in the year 2016-2017. The qualitative analysis showed financial and non financial barriers played role in service accessibility. Regarding the non financial barrier, poor communication due to inaccessible geography was the key player in accessibility. Conclusion: The lack of skilled human resources as well as the poor communication due to inaccessible geographical location is the most important reason behind the poor UHC in the block.